Resveratrol targeting MDM2/P53/PUMA axis to inhibit colonocyte apoptosis in DSS-induced ulcerative colitis mice - Rui Tang; Rui Tang; Ling Jiang; Quan Ji; Pengyuan Kang; Yuan Liu; Pengyu Miao; Xiaofan Xu; Mingxi Tang; Mingxi Tang; Mingxi Tang (Frontiers in Pharmacology)
BackgroundResveratrol, a naturally occurring polyphenolic compound found in grapes, berries, and traditional medicinal plants like Polygonum cuspidatum, has been used for centuries in traditional medicine systems for its anti-inflammatory, antioxidant, and cardioprotective properties. Ulcerative colitis (UC), a chronic inflammatory bowel disease, is characterized by intestinal barrier disruption due to excessive colonocyte apoptosis, leading to increased permeability and inflammation. Targeting apoptosis is a critical therapeutic strategy for UC.Aim of the studyThis study aims to investigate the therapeutic potential of Resveratrol in ulcerative colitis (UC) by targeting excessive colonocyte apoptosis and intestinal barrier dysfunction. Specifically, we seek to elucidate the mechanisms through which Resveratrol modulates apoptosis-related pathways and evaluate its efficacy in restoring intestinal homeostasis and mitigating UC progression in both in vivo and in vitro models.Materials and MethodsWe used dextran sulfate sodium (DSS) to induce UC in a mouse model. Colonic damage was assessed through colonic length measurement, histological examination, and immunofluorescence staining. Single-cell sequencing was employed to explore changes in the colonic immune microenvironment and cellular signaling pathways after Resveratrol treatment. In vitro, colonocytes isolated from healthy mouse colonic tissue were exposed to TGF-β to induce apoptosis. DNA fragmentation, mitochondrial membrane potential, and annexin V/propidium iodide staining were used to assess apoptosis. Additionally, we employed an Adeno-Associated Virus system to overexpress MDM2 in the colon and evaluate its protective role in DSS-induced UC.ResultsResveratrol treatment effectively repaired colonic damage in the UC mouse model by significantly increasing colon length, reducing inflammatory cell infiltration, and mitigating mucosal injury. Single-cell sequencing revealed that Resveratrol primarily targeted colonocytes, decreasing genes related to apoptosis and the P53 pathway. In vitro, Resveratrol reduced DNA fragmentation, apoptotic cell populations, and increased mitochondrial membrane potential in a dose-dependent manner. Furthermore, Resveratrol increased MDM2 expression, inhibiting P53 and downstream pro-apoptotic signaling. Nutlin-3a, an MDM2 inhibitor, reversed the anti-apoptotic effects of Resveratrol. Overexpression of MDM2 in the colon protected against DSS-induced damage.ConclusionResveratrol is an effective treatment for DSS-induced UC, primarily by inhibiting excessive apoptosis in colonocytes through the MDM2/P53/PUMA axis. MDM2 presents a promising therapeutic target for UC treatment.